1997
DOI: 10.1210/endo.138.5.5095
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-6 in the Induction of Hypercalcemia in Renal Cell Carcinoma Transplanted into Nude Mice

Abstract: The role of interleukin-6 in the induction of hypercalcemia in renal cell carcinoma transplanted into nude mice Weissglas, M.G.; Schamhart, D.H.J.; Lowik, C; Papapoulos, S.; Theuns, H.; Kurth, K-H. Published in: Endocrinology DOI:10.1210/en.138.5.1879 Link to publication Citation for published version (APA):Weissglas, M. G., Schamhart, D. H. J., Lowik, C., Papapoulos, S., Theuns, H., & Kurth, K-H. (1997). The role of interleukin-6 in the induction of hypercalcemia in renal cell carcinoma transplanted into nude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…In contrast, tumors continued to grow in control mice that were injected with physiological saline without endostatin ( Figure 7A). The RC-9 tumor produces interleukin-6 and parathyroid hormone-like protein (PTHrP) and therefore causes hypercalcemia and hypophosphatemia (Weissglas et al, 1995(Weissglas et al, , 1997. As expected, when serum levels of calcium and phosphate were determined at the end of the experiment, endostatin-treated animals had lower calcium levels and higher phosphate levels than animals in the control group ( Figure 7B and C).…”
Section: Anti-tumor Activities Of Mutant Endostatin With No Zinc Bindingsupporting
confidence: 60%
“…In contrast, tumors continued to grow in control mice that were injected with physiological saline without endostatin ( Figure 7A). The RC-9 tumor produces interleukin-6 and parathyroid hormone-like protein (PTHrP) and therefore causes hypercalcemia and hypophosphatemia (Weissglas et al, 1995(Weissglas et al, , 1997. As expected, when serum levels of calcium and phosphate were determined at the end of the experiment, endostatin-treated animals had lower calcium levels and higher phosphate levels than animals in the control group ( Figure 7B and C).…”
Section: Anti-tumor Activities Of Mutant Endostatin With No Zinc Bindingsupporting
confidence: 60%
“…26 Weissglas et al suggested that IL-6 might have enhanced hypercalcemia by stimulating the tumor growth of a subpopulation of PTHrP-secreting renal carcinomas. 12 This is not in agreement with the present study, in which the SMRC-3 cell line produced more IL-6 and grew faster than SMRC-1 but turned out to secrete less PTHrP. These findings suggest that IL-6 promoted tumor growth by a non-selective autocrine mechanism.…”
Section: Discussioncontrasting
confidence: 96%
“…Parathyroid hormone-related protein has been reported to be released in some new cell lines of human kidney and lung cancer in culture. 12,13 However, the patients from whom these cell lines have been isolated have not necessarily presented with hypercalcemia and the contribution of PTHrP to calcium homeostasis in the tumors remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that IL-6 stimulates tumor growth. 34,35 It is not clear whether this cytokine causes hypercalcemia either directly or indirectly by increasing the effect of PTHrP on bone resorption. [36][37][38] At this time, IL-6-mediated hypercalcemia appears to be multifactorial.…”
Section: Discussionmentioning
confidence: 99%